2016
DOI: 10.1515/jpm-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Biological and biochemical characteristics of a Mediterranean population with Gestational Diabetes Mellitus

Abstract: The interplay of various nutrients provided to the developing foetus determines the growth potential of the conceptus. This study assessed the inter-relationship between these nutrients in a Mediterranean population including 1062 pregnant, previously non-diabetic women. These underwent an oral glucose tolerance test (oGTT) and were accordingly classified into gestational hyperglycaemic and normoglycaemic groups. Fasting insulin, HbA1c, and lipid profiles were further assessed, and the anthropomorphic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…It is generally accepted that both an increase in maternal age and BMI are associated with an elevated risk of developing GDM . Our findings are in line with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…It is generally accepted that both an increase in maternal age and BMI are associated with an elevated risk of developing GDM . Our findings are in line with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…While documenting biologic and biochemical characteristics of a Mediterranean population with GDM, Savona-Ventura et al, found increased maternal age, increased pre-pregnancy weight, and increased weight gain in pregnancy were seen in the GDM group [7]. The implication that pre-pregnancy weight loss could reduce the incidence of GDM is supported by this study.…”
supporting
confidence: 71%
“…Of the 13,705 unique records identified by the searches, 46 publications reporting from 42 studies were included in the review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The number of pregnancies ranged from 38 to 5,535. On the basis of the World Bank Income Classification of countries , 25 out of 42 studies were from high‐income economies , 16 from upper‐middle‐income economies and 1 from middle‐income economies . Forty studies were prospective cohorts , three were retrospective cohorts and three were secondary analyses of cohorts in RCTs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation